2017
DOI: 10.1039/c7ra01720k
|View full text |Cite
|
Sign up to set email alerts
|

Kx(C2H8N2)yFe2−zS2: synthesis, phase structure and correlation between K+ intercalation and Fe depletion

Abstract: Co-intercalated FeS Kx(C2H8N2)yFe2−zS2 has been synthesized by a sonochemical method. It has been found that the charged K+ intercalation depleted the Fe from [FeS] layers, resulting in disordered Fe vacancies and weak ferrimagnetic semiconducting behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This unit cell dimensions are in close agreement with literature reports on alkali metal and alkali metal-free ethylenediamine intercalated FeS. 14,15,24,59 There is one impurity peak seen in the PXRD due to excess Fe powder remaining from the in situ growth of FeS layers. To avoid excess Fe, we attempted syntheses using pre-reacted tetragonal FeS at 120 °C over 2–6 days, but were unsuccessful.…”
Section: Resultssupporting
confidence: 90%
“…This unit cell dimensions are in close agreement with literature reports on alkali metal and alkali metal-free ethylenediamine intercalated FeS. 14,15,24,59 There is one impurity peak seen in the PXRD due to excess Fe powder remaining from the in situ growth of FeS layers. To avoid excess Fe, we attempted syntheses using pre-reacted tetragonal FeS at 120 °C over 2–6 days, but were unsuccessful.…”
Section: Resultssupporting
confidence: 90%
“…The composition was measured by EDS, and the result was determined to be Cs 0.9(1) Ni 3.3(1) Se 3 (see Figure S3), which is consistent with the nonstoichiometric feature from the synthesis. It is worth noting that, as far as we know, Cs 0.9 Ni 3.1 Se 3 is the first nonstoichiometric compound in the TlFe 3 Te 3 -type family, although nonstoichiometry is common in quasi-2D TMX systems. , It has been demonstrated that a certain extent of deviation from the stoichiometry is required for phase stabilization in some 2D-layered structures. , In Cs 0.9 Ni 3.1 Se 3 , the extra Ni atom may play the same role in stabilizing the structure. On the other hand, Neilson et al reported that, by deintercalating K in the ThCr 2 Si 2 -type KNi 2 Se 2 , the structure switched to the NiAs type with face-sharing NiSe 6 octahedra .…”
Section: Resultsmentioning
confidence: 99%
“…92,133,136,137 Similar to FeSe, FeS can also act as a host for guest species such as alkali cations with nonaqueous solvents. Guo et al 138 recently intercalated FeS with K + in EDA. Unlike the its Se analogues, however, the EDA-intercalated sulfide is not superconducting.…”
Section: ■ Intercalation Chemistrymentioning
confidence: 99%